Relationships between oxygen changes in the brain and periphery following physiological activation and the actions of heroin and cocaine - Shruthi A. Thomas (Nature Portfolio, 2021)
Abstract Using two-sensor electrochemical recordings in freely moving rats, we examined the relationship between physiological and drug-induced oxygen fluctuations in the brain and periphery. Animals chronically implanted with oxygen sensors in the nucleus accumbens (NAc) and subcutaneous (SC) space were subjected to several mildly arousing stimuli (sound, tail-pinch and social interaction) and intravenous injections of cocaine and heroin. Arousing stimuli induced rapid increases in NAc oxygen levels followed by and correlated with oxygen decreases in the SC space. Therefore, cerebral vasodilation that increases cerebral blood flow and oxygen entry into brain tissue results from both direct neuronal activation and peripheral vasoconstriction, which redistributes arterial blood from periphery to the brain. The latter factor could also explain a similar pattern of oxygen responses found in the substantia nigra reticulata, suggesting hyperoxia as a global phenomenon with minor structural differences during early time intervals following the stimulus onset. While arousing stimuli and cocaine induced similar oxygen responses in the brain and SC space, heroin induced a biphasic down-up brain oxygen fluctuation associated with a monophasic oxygen decrease in the SC space. Oxygen decreases occurred more rapidly and stronger in the SC space, reflecting a drop in blood oxygen levels due to respiratory depression.